The design of hermeneutic dialogues with graphic design: The process of interpretation - Vilchis Esquivel , Luz del Carmen (Seven Editora, 2023)
The graphic designer makes important decisions during the methodological process, with interpretations based on the concept of dialogue. The users or receivers of the messages also interpret these messages through questions and answers. These dialogic situations are conditioned by semeiotic elements that are determined by objects, contexts and preconceived opinions, which are considered by the hermeneutic models that allow explaining disciplines that, like graphic design, cannot be studied through scientific methods. This can be explained by visualizing the fragments of the process of visual communication as a spiral in constant movement (an idea that surpasses the classical hermeneutic circle) in a sequence of spheres or moments that spin in time and space, as in Sloterdijk’s spheres theory, which means a contemporary way of looking at globalization. Likewise, it is a new way of approaching the theory of graphic design from a philosophical point of view that conducts conceptual relations that consider the concept of design as a particle in a universe of knowledge. Along this line of research, this is the way to direct design toward humanism, as an inescapable compromise with the human being and the future horizons of the visual culture. DOI:https://doi.org/10.56238/interdiinovationscrese-047